Pentingnya Kebersihan dalam Perspektif Islam : Pendekatan Holistik untuk Kesehatan Fisik dan Spiritual - Alya Nuralifya; Ditya Taftazani Sukarmo Putri; Fina Oktavi Rahman; Fitri Auliani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The findings highlight the need for faith-based hygiene education and community involvement in hygiene practices to improve physical and spiritual health among Muslims. This study used quantitative methods with data collection instruments in the form of questionnaires. The number of respondents in this study was 31 people from various backgrounds. The selection of this method aims to objectively measure the increase in community participation in environmental cleanliness and its relation to the Islamic understanding that cleanliness is part of faith. This method was chosen to provide a clear picture of respondents' perceptions, appreciation, experiences, and assessments of aspects of environmental cleanliness and religious understanding. The study found that the majority understood cleanliness as part of faith. These results emphasize the need for faith-based hygiene education and community participation in hygiene practices.